JACK M. SASSON. From the Mari Archives: An Anthology of Old Babylonian Letters. Winona Lake, Eisenbrauns, 2015. xx + 454. ISBN 1–57506–830–3. $ 59.50 - Freire, Lucas G. (2016)
Fil: Freire, Lucas G. North-West University; Sudáfrica